Marketing effectiveness of Islamic and conventional banks: evidence from Malaysia - Habibullah, Muzafar Shah; Abdul Hamid, Baharom; Syed Najibullah (Palgrave Macmillan-Springer Nature, 2017)
The study aims to address marketing effectiveness of both Islamic banks and conventional banks (CBs) by using a modified “chain-of-effect” framework. Against current literature, which is based on customer surveys, reports do not include marketing activities by the Islamic banks (IB); this study adopts a bank perspective to explore the IB’s behavior in this regard. Applying fixed-effect panel regression on the quarterly data of five IBs and five CBs in Malaysia, the study aims to explore the influence of marketing efforts on performance (both financial and nonfinancial) and if such relation varies by the type of banks in Malaysia. The findings of the study show that IBs are performing well in using marketing efforts to generate meaningful financial and nonfinancial performance.